SERVICE QUALITY OF TEACHING HOSPITAL FROM PATIENT PERSPECTIVE A SCOPING REVIEW - alkaf, syifa; Amal Chalik Sjaaf (Majalah Kedokteran Sriwijaya, 2023)
Teaching hospitals must have high standards in terms of service, and latest technology, while still be able to accommodate a wide range of interests in terms of education, teaching and research. Teaching hospitals have long been known as hospitals with tiered, comprehensive, technologically advanced- business, but requiring longer time for delivering services. Patients today are more informed and educated about the quality of health care than they were in the past. This istudy iaimed ito iidentify iand evaluate ipublished iresearch ion ihow ipatient iperceive ito iservice iquality iin iteaching ihospital iin various icountries. iProQuest iand iEBSCOhost idatabases iwere iused ifor iarticle isearch iand iPRISMA flow idiagram iwas iused ito iperform ithe iarticles iselection. iThe isearch iresulted i515 iarticles iselected. Title iand iabstract iscreening iremoved iselected iarticles, ileaving i19 iassessed ifor ieligibility. iArticles relevant ito ithe istudy iquestion iand imeet ithe icriteria iwere i10 iarticles. iMost iof ithe istudies iwere conducted iin ideveloping icountries. iResults iof ithe istudy ishowed ithere is a strong relationship between quality of service provided with level of satisfaction reported by patients. most studies agreed physician variable to be the most significant determinant to patient’s perceived quality of care, while physical environment and administrative services also supported positive response. The findings provide healthcare managers as well as academic physicians, and university leader with valuable information regarding the variables associated with patient satisfaction to service care of teaching hospital. This knowledge equips them with the ability to better address and fulfill the needs and preferences of patients.